2020
DOI: 10.1080/02670844.2020.1730061
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of excellent anti-corrosion epoxy coating based on GON-An composites

Abstract: Polyaniline/graphene oxide (GON-An) composites were synthesized by chemically grafting pphenylenediamine (PPDA)-modified graphene oxide (GO) with polyaniline (PANI), which was confirmed by FT-IR, XRD, SEM, TEM, Raman spectroscopy, and XPS analyses. The electrochemical impedance spectroscopy test, brine immersion, and Tafel slopes analysis revealed that compared with GO and PPDA-modified GO (GON), GON-An composites which combined the unique corrosion resistance of both PANI and GO exhibited relatively obvious s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In addition, the Bode plots of our different coatings at 0.1 Hz after one day of immersion show that E/PANI–PGO (0.2) has the highest quality amongst all of the coatings as this coating has a corrosion resistance 230.64 times higher than that of bare epoxy. Comparing our present results to a similar report by Wang et al , it was shown that the best corrosion resistance achieved by their nanocomposite (GON–An02E) raised the corrosion resistance up to 30.15 times more than that of bare epoxy at 0.01 Hz after one day of immersion in brine, 47 which is far less than our reported value. This demonstrates the excellent anti-corrosion behavior of the nanocomposites prepared in this work.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, the Bode plots of our different coatings at 0.1 Hz after one day of immersion show that E/PANI–PGO (0.2) has the highest quality amongst all of the coatings as this coating has a corrosion resistance 230.64 times higher than that of bare epoxy. Comparing our present results to a similar report by Wang et al , it was shown that the best corrosion resistance achieved by their nanocomposite (GON–An02E) raised the corrosion resistance up to 30.15 times more than that of bare epoxy at 0.01 Hz after one day of immersion in brine, 47 which is far less than our reported value. This demonstrates the excellent anti-corrosion behavior of the nanocomposites prepared in this work.…”
Section: Resultssupporting
confidence: 56%
“…However, it was shown that increasing the amount of aniline did not improve the resistance of the material against corrosion. 47 A comparison between the most efficient coating in this research and the other reported results is summarized in Table S1. † Our results not only detail the dual-functionality of epoxy-based coatings, of both anti-corrosion and anti-fouling properties, but we also aimed to investigate the effects of other synthesis parameters, such as changing the ratio of PPDA to GO, changing the loading of functionalised GO, the synthesis method, and the type of epoxy with lower resistance that provided better functional properties.…”
Section: Introductionmentioning
confidence: 91%
“…Gao et al prepared a graphene oxide-based PANI composite for waterborne polyurethane, and the coating exhibited enhanced corrosion resistance due to the synergistic effect between the physical barrier of graphene and the passivation mechanism of PANI. Wang et al synthesized PANI/GO composites by chemically grafting phenylenediamine-modified GO with PANI. The EP coating with added composites exhibited excellent corrosion resistance in electrochemical tests and salt spray tests.…”
Section: Introductionmentioning
confidence: 99%
“…International and national legislation prospect of decreasing the volatile organic compounds (VOCs) has prompted significant modification in the design of anticorrosive coatings as conventional anticorrosive coatings are having a comparatively higher percentage of solvents. The current environmental pressure to decrease discharges of VOCs has encouraged the coating industry to promote and develop coatings with a low or nil percentage of organic solvent [4][5][6].…”
Section: Introductionmentioning
confidence: 99%